1996
DOI: 10.1021/la9601667
|View full text |Cite
|
Sign up to set email alerts
|

Metal−Oxygen Cluster Compounds (Heteropoly Oxometalates) of 1B and 3B Monovalent Cations and Their Micropore Structure

Abstract: Silver and thallium, representatives from the periodic table's groups 1B and 3B, respectively, were employed as cations to synthesize stoichiometric and nonstoichiometric salts of 12-tungstophosphoric, 12-molybdophosphoric, and 12-tungstosilicic acids. All the solids, except silver 12-molybdophosphate, have high surface areas and microporous structures, as shown from the analysis of nitrogen adsorptiondesorption isotherms obtained at 77 °K. Powder X-ray diffraction, temperature-programmed desorption, infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 24 publications
(36 reference statements)
0
4
1
Order By: Relevance
“…Therefore NLDFT methods are likely more accurate in the reporting of phosphomolybdate surface areas, despite BET values being commonly reported. The NLDFT surface areas ranged from 0.387 to 28 [27,36,98], although work by Okuhara et al supports our finding [41]. The surface area also decreases with respect to increased cation size, which also contrasts with established findings [25,30,37,38,64].…”
Section: Discussioncontrasting
confidence: 85%
“…Therefore NLDFT methods are likely more accurate in the reporting of phosphomolybdate surface areas, despite BET values being commonly reported. The NLDFT surface areas ranged from 0.387 to 28 [27,36,98], although work by Okuhara et al supports our finding [41]. The surface area also decreases with respect to increased cation size, which also contrasts with established findings [25,30,37,38,64].…”
Section: Discussioncontrasting
confidence: 85%
“…1B II), in agreement with those referred to in the literature [23] for this heteropolyacid. The first band is not assigned, while the others are ascribed to the stretching vibrations ence between the Al 3+ and [H 5 O 2 ] + cations, as was reported for diverse salts in the literature, where the variations in the lattice parameters have been attributed to such difference [25]. Instead, the diffraction pattern of the Cu 2+ salt (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…It is evident that transformation of the HPA to the corresponding oxides is modified by the presence of these cations and the stability of the intermediate species between the hydrated form of the HPA and the increase in crystallized molybdenum oxide in the presence of the metal counterions. Earlier work has shown that the salts of the heteropoly acids prepared with monovalent cations have a higher thermal stability than those of the parent acids.…”
Section: Discussionmentioning
confidence: 99%